2020
DOI: 10.1007/s00005-020-00582-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Immunomodulatory Agents to Induce Human T Regulatory (Treg) Cells: Preferential Treg-Stimulatory Effect of Prednisolone and Rapamycin

Abstract: T regulatory (Treg) cells play a critical role in the maintenance of self-tolerance, as well as in inhibition of inflammation and exaggerated immune response against exogenous antigens. They develop in the thymus (tTreg cells) but also may be generated at the peripheral tissues, including tumor microenvironment (pTreg cells), or induced in vitro in the presence of transforming growth factor (TGF)-β (iTreg cells). Since tTreg cells constitute a minor fraction of peripheral blood lymphocytes in physiological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Rapamycin-treated PBMCs didn't exhibited differences on the frequency and functions of regulatory T cells (Tregs), which may probably due to the insufficient time and lack of added Treg inducers (TGFB, IL2, etc.) (21,22) (Supplemental Figure 4).…”
Section: Rapamycin Decreased the Frequency Of Cd4+ Ctls In Pbmcs Of G...mentioning
confidence: 99%
“…Rapamycin-treated PBMCs didn't exhibited differences on the frequency and functions of regulatory T cells (Tregs), which may probably due to the insufficient time and lack of added Treg inducers (TGFB, IL2, etc.) (21,22) (Supplemental Figure 4).…”
Section: Rapamycin Decreased the Frequency Of Cd4+ Ctls In Pbmcs Of G...mentioning
confidence: 99%
“…Treatment of ENL with prednisolone is associated with an increased proportion of Tregs which leads to the inhibition of inflammation [ 49 ]. It is suggested that prednisolone controls inflammation via TGFβ and TGFβ suppresses the functions of Th1 effector cells and promotes the generation of Tregs [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that mTOR inhibition can expand the number of Tregs regardless of antigen levels. [46][47][48][49] In a transforming growth factor-β (TGF-β)-dependent manner, an mTOR-I enhanced the expression of Foxp3. 50 Tregs that are expanded by an mTOR-I suppress the proliferation of both syngeneic and allogeneic CD4 + and CD8 + T cells in vitro and prevent allograft rejection in vivo.…”
Section: Induction Of T Regulatory Cells (Tregs) and Tolerancementioning
confidence: 99%